Comparative analysis of extractive and pressure swing distillation for separation of THF-water separation - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Computers & Chemical Engineering, 2017)
In the present work, extractive and pressure-swing distillation methods are analyzed in detail through steady state ASPEN Plus simulations to propose the most economic method for separation of equimolar mixture of THF-Water. Various solvents were evaluated and DMSO was identified as the most appropriate solvent, as it gave minimum Total Annual Cost (TAC) for desired purity. In case of pressure swing distillation, various pressure ranges were explored to achieve minimum TAC. Configurations for extractive and pressure swing distillation with heat integration were also worked out. The optimum designs of extractive and pressure swing distillation with and without heat integration were compared on a common basis of feed conditions and purity constraints. Results indicate that TAC of extractive distillation with heat integration is 5.2% less than that of PSD with partial heat integration. (C) 2017 Elsevier Ltd. All rights reserved.

Study of the effect of operating parameters on the extractive distillation of isopropyl alcohol–water mixture using dimethyl sulphoxide as an entrainer - Ghuge, Pravin D.; Mali, Nilesh A.; Sirsam, R. S. (Indian Chemical Engineer, 2017)
Abstract: In this paper, the simulation analysis of separation of isopropyl alcohol (IPA)–water via extractive distillation by using dimethyl sulphoxide as an entrainer is presented. The steady-state simulation for this process was done using Aspen Plus simulator. The aim of this work is to study the effect of various operating parameters such as number of stages, molar reflux ratio, binary feed stage number, entrainer feed stage number, temperature of entrainer feed and entrainer to feed molar ratio on the purity and energy consumption. The sensitivity of these parameters serves as a basis to choose the optimum operating conditions to maximize the IPA purity and minimize the energy requirement. In this analysis, among various operating parameters, those which directly affect the IPA purity and the parameters which affect the reboiler duty, for the given separation task, are identified. Simulation results with optimum operating conditions and their economic analysis are also presented.
Keywords: Aspen Plus Simulators; Azeotrope; Computer software; Distillation; Energy requirements; Energy utilization; Extractive distillation; Isopropyl alcohol/water; Isopropyl alcohols; Operating parameters; Optimum operating conditions; Sensitivity analysis; simulation; SimulationSteady-state simulations; Solvents

Vapor-liquid equilibrium data for binary mixtures of dimethyl carbonate with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate at 93.13 kPa - Mali, Nilesh A.; Yadav, Satyajeet S.; Ghuge, Pravin D.; Joshi, Sunil. S. (Journal of Chemical and Engineering Data, 2017)
Isobaric vapor-liquid equilibrium (VLE) data was measured at the local atmospheric pressure of 93.13 kPa for the binary systems of dimethyl carbonate (DMC) with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate using a dynamic recirculation still. VLE data was generated in the form of T-x,y and was checked for thermodynamic consistency using the Herington area test, Van Ness test, and mean absolute deviation between experimental and calculated total pressure and vapor phase composition. Data for all pairs meet the criteria for thermodynamic consistency and were found suitable for process modeling. Binary interaction parameters for the Wilson, nonrandom two-liquid (NRTL), and universal quasichemical (UNIQUAC) activity coefficient models were determined using the objective function of minimizing the deviation between the experimental and the calculated vapor phase composition and total pressure. For all binary systems, Wilson, NRTL, and UNIQUAC models gave good predictions. Azeotropic behavior was observed for the isopropyl acetate-DMC pair at 357.8 K and 0.6 mole fraction of isopropyl acetate.

Extractive distillation configuration for nitric acid dehydration using sulfuric acid as a solvent - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Industrial & Engineering Chemistry Research, 2020)
In this work, an extractive distillation configuration for dehydration of nitric acid is proposed with sulfuric acid as a solvent. Thermodynamic modeling of the vapor-liquid equilibrium of binary and ternary systems of nitric acid/water/sulfuric acid is carried out using the electrolyte non-random two-liquid (eNRTL-RK) thermodynamic property method in the Aspen plus process simulator. The model performance is validated by comparing the experimental data with the estimated data by the eNRTL-RK model and is found to be in good agreement. The thermodynamic model is then used for developing a triple-column extractive distillation sequence, comprising a preconcentration column, an extractive distillation column, and a solvent recovery column. The configuration is designed, simulated, and optimized to concentrate dilute nitric acid using sulfuric acid as a solvent to break the nitric acid-water azeotrope. The operating and structural parameters of the distillation configuration are optimized simultaneously with an objective of minimizing the energy consumption and the total annual cost (TAC) of the overall configuration.

Effect of CaCl2 and ZnCl2 salts on isobaric vapor-liquid equilibrium in separation of the azeotropic mixture of ethanol plus water - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Fluid Phase Equilibria, 2021)
Present work analyzes potential of calcium chloride (CaCl2) and zinc chloride (ZaCl(2)) salts as entrainer for breaking the minimum boiling azeotrope of ethanol and water. Isobaric vapor-liquid equilibrium (VLE) data for the binary systems of water + ethanol and ternary system of water + ethanol + calcium chloride, and water + ethanol + zinc chloride were measured at a constant pressure of 94.5 kPa. The effect of salts on the relative volatility of ethanol to water as well as on the vapor phase mole fractions of ethanol were also studied experimentally. From the experimental results, it is observed that with addition of salts, the azeotropic point of the ethanol and water system can be eliminated. Salting out effects in case of calcium chloride was more than that zinc chloride salt. The results obtained in this work showed that calcium chloride could be a better choice for separation of the water + ethanol azeotrope. Electrolyte nonrandom two-liquid (eNRTL) model was used to correlate the experimental VLE data. The model prediction with the regressed parameters was found in well agreement with the experimental data. The experimental data obtained in this work was found thermodynamically consistent using van Ness test. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azeotrope; eNRTL; Ethanol; salts; Vapor-liquid equilibrium; Water

Isobaric vapor-liquid-equilibrium data measurement of toluene with ethyl acetate, n-Propyl Acetate, Iso-propyl Acetate, Iso-butyl Acetate, and Iso-amyl Acetate: experiments and modeling - Sutar, Dipak S.; Mali, Nilesh A.; Ghuge, Pravin D. (Journal of Chemical and Engineering Data, 2025)
The isobaric vapor-liquid equilibrium (VLE) data of the systems (ethyl acetate + toluene), (n-propyl acetate + toluene), (iso-propyl acetate + toluene), (toluene + iso-butyl acetate), and (toluene + iso-amyl acetate) were measured under the isobaric condition at 92 kPa using a glass dynamic recirculation apparatus. The experimental VLE data was correlated by NRTL, Wilson, and UNIQUAC activity coefficient models to account for the nonideality. The binary interaction parameters of the models were obtained by regressing the experimental data using the maximum likelihood objective function. The thermodynamic consistency of the experimental data was checked by using the Van Ness test and the infinite dilution test. Extrapolating the activity coefficient at infinite dilution was done by regressing the experimental data with an extended Redlich-Kister equation. The NRTL, Wilson, and UNIQUAC models exhibited a maximum root-mean-square deviation less than unity for temperature and vapor mole fraction. Additionally, it is worth noting that no azeotrope was identified in the VLE data in this study.